2021
DOI: 10.1080/02656736.2021.1912414
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for treatment of thyroid follicular neoplasm with low SUV in PET/CT study

Abstract: Objectives: To evaluate the feasibility of radiofrequency ablation (RFA) on follicular neoplasm with low standard uptake value (SUV) in a Positron emission tomography (PET/CT) study. Methods: From January 2018 to July 2019, 86 consecutive patients were diagnosed with follicular neoplasm. Of the patients, 28 with PET/CT scans were enrolled in this study. All patients received ultrasound, fine/core needle aspiration, and PET/CT scan prior to treatment. In accordance with previous studies, we recommended 6 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Of these patients, 23 who refused surgery or were at a high risk of surgery were actively followed up, with a median duration of 3.5 years during which no evidence of tumor progression was observed. However, active surveillance may cause anxiety in patients, which probably impairs patients' quality of life and compliance with follow-up (23). In the present study, 44/85 (51.76%) of Bethesda IV thyroid in the surgery group were diagnosed as benign lesions, involving 29 cases of FTA, nine nodular goiters, and six lymphocytic thyroiditis.…”
Section: Discussionmentioning
confidence: 55%
“…Of these patients, 23 who refused surgery or were at a high risk of surgery were actively followed up, with a median duration of 3.5 years during which no evidence of tumor progression was observed. However, active surveillance may cause anxiety in patients, which probably impairs patients' quality of life and compliance with follow-up (23). In the present study, 44/85 (51.76%) of Bethesda IV thyroid in the surgery group were diagnosed as benign lesions, involving 29 cases of FTA, nine nodular goiters, and six lymphocytic thyroiditis.…”
Section: Discussionmentioning
confidence: 55%
“…Several works have reported an overall acceptable experience with indeterminate thyroid nodule RFA. Most recently, Lin et al treated 22 follicular neoplasms and reported a volume reduction of 73.3% at 6–12 months [ 24 ]. The authors reported only a single complication of temporary (3 months) vocal cord palsy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Lin et al treated 22 follicular neoplasms and reported a volume reduction of 73.3% at 6–12 months [ 24 ]. The authors reported only a single complication of temporary (3 months) vocal cord palsy [ 24 ]. A separate work of 10 small (<2 cm) follicular neoplasms were treated by RFA and achieved VRRs of 99.5%, with eight lesions disappearing completely.…”
Section: Discussionmentioning
confidence: 99%
“…The (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET) is non-invasive, and a nodule with an SUVmax ≥5 is highly indicative of malignancy, with a sensitivity of 76% and A c c e p t e d A r t i c l e specificity of 85% [118]. There is increasing evidence noting the differentiation between Hürthle cell carcinoma and follicular adenomas on PET [119,120]. In a study enrolling 46 patients with indeterminate results on FNA, which surveyed the efficacy of PET/CT for detection of malignant lesions, the values for the sensitivity and specificity, and the positive predictive and negative predictive values were 94%, 62%, 59%, and 95%, respectively [121].…”
Section: A C C E P T E D a R T I C L E (Strong Recommendation Moderat...mentioning
confidence: 99%
“…In a study enrolling 46 patients with indeterminate results on FNA, which surveyed the efficacy of PET/CT for detection of malignant lesions, the values for the sensitivity and specificity, and the positive predictive and negative predictive values were 94%, 62%, 59%, and 95%, respectively [121]. Pre-ablative FDG-PET is helpful for further assessment of malignant FDG-avid LNs in patients with PTMC/PTC [117,120].…”
Section: A C C E P T E D a R T I C L E (Strong Recommendation Moderat...mentioning
confidence: 99%